'n Optimale inkomsteverdelingsbeleid vir koöperasies - W. D. Hamman; I. J. Lambrechts (South African Journal of Business Management, 1985)
– An optimal income appropriation policy for a co-operativeThe income (after interest payable, except on deferred bonuses and before taxation) can be appropriated in three different ways (different combinations are possible), i.e. the payment of cash bonuses, the declaration of deferred bonuses, and the conversion of deferred bonuses in shares. Each of these methods has different cash flow and tax consequences for a co-operative and its shareholders. Each of the above-mentioned methods results in a tax deduction for a co-operative and an increase in taxable income for the member even if there is no cash inflow. Interest and dividends as compensation also have different tax consequences for both the co-operative and its members. To determine the optimal income appropriation policy a long term cash flow model is developed to establish the effect of a specific policy on the cash position of both the co-operative and the member. The co-operative also has to watch its solvency carefully. The marginal tax rate of the member also plays an important role.
Keywords: 650